(untitled) (Per Musi, 2021)
Singers perform different vocal adaptations to sing both lyrical and popular music. The mechanism M1 (modal register) is predominant, but a small portion uses the mechanism M2 (falsetto register). In the lyrical singing, it is the countertenor who makes this peculiar vocal emission. The present study analyzed through nasofiberscopic, glottic, and supraglottic adjustments performed by countertenors, as well as the presence and level of the singer’s formant. The tasks (two interval leaps - a minor sixth and a perfect fourth – and a crescendo in sustained note) were taken from an aria by Georg Friedrich Haendel. During the crescendo, a lowering of the larynx and pharyngeal widening were observed; pharyngeal constrictions and laryngeal elevation were observed in both leaps executions; no glottal chink or air leak were detected. Singer’s formant was identified on all subjects. Professional countertenors performed better than non-professional because they had a higher level of singer’s formant and, supralaryngeal adjustments that favor vocal emission with less constrictions and a higher degree of larynx lowering, therefore compatible with better vocal emission.